Effective Way of Conducting Laboratory Classes for Engineering Students - Naskar, M. K. (Journal of Engineering Education Transformations, 1995)
The purpose of including laboratory classes in the engineering curriculum is to supplement as well as to verify and extend the knowledge obtained from the theory classes. Engineering students must have confidence and skill to develop engineering products which cannot be built up without laboratory classes and hence laboratory classes have some added importance compared to the theory classes.